Green manure - corn rotation and phosphorus adsorption in an Oxisol - Naves Silva, Marx Leandro; Curi, Nilton; Blancaneaux, Philippe; de Lima, José Maria; de Carvalho, Arminda Moreira (Pesquisa Agropecuaria Brasileira, 1997)
The objectives of this study were to quantify the P adsorption maximum in different green manure cropping systems and to evaluate the influence of the decomposition rate of green manure and some soil chemical properties upon such adsorption. It was studied the 0 to 20 cm layer of an Oxisol (Dark Red Latosol) under the following treatments: soil under native cerrado, bare soil (five years) and the following green manure cultivated in the dry season, after corn (cv. Pioneer 3072): Crotalaria juncea, Cajanus cajan, Mucuna aterrima and Brachiaria ruziziensis. The adsorption values were adjusted to Langmuir isoterm for determination of P adsorption maximum capacity (PAMC). The general trend of the P maximum adsorption followed the order: discovered soil > Cajanus cajan > Crotalaria juncea > Mucuna aterrima > Brachiaria ruziziensis > native cerrado. Soil organic matter amount and green manure decomposition rate had negative correlation with the P maximum adsorption, with correlation coefficients of 0.705 (P < 0.06) and 0.983 (P < 0.01), respectively. The PAMC for the deepest layer was 56% higher than that of the superficial layer, suggesting the importance of organic matter on reducing P adsorption.